The Role of Regional Bawaslu as a Supervisor in the Prevention and Hndling of Election Administration Violations in the City of Sukabumi - Ana Maria (Rechtsnormen: Journal of Law, 2023)
Background.  General elections are held simultaneously, including the election of members of the House of Representatives, members of the Regional Representative Council, President and Vice President, and to elect members of the Regional People's Representative Council, where in each process towards general elections there are several stages that need to be carried out by election participants. Purpose. In the general election stages, there are often negligence committed by election participants, one of which is election administration violations, election administration violations are violations committed by election participants or election organizers during the election stages. Method. In this research, the author uses normative juridical research methods that are qualitative in nature. Results. Based on the findings made by the Sukabumi City Bawaslu, there were 19 findings of administrative violations in Sukabumi City committed by 2019 election participants, including 16 violations of campaign props and 3 violations of campaigns without notification letters to the police. From the findings by the Sukabumi City Bawaslu related to administrative violations, the Sukabumi City Bawaslu is authorized to receive, examine, review, decide reports from the public or findings by the Election Supervisor related to alleged election administration violations. From the alleged violation of election administration, the settlement uses a fast event in accordance with Article 40 of Perbawaslu No. 8 of 2022. From the many findings of alleged election administration violations, Bawaslu of Sukabumi City made several prevention efforts including appeals, Bawaslu of Sukabumi City delivered appeals to the community, election officials, and election officials. Conclusion. Socialization, namely the implementation of the initialization of election rules and regulations and coordination to the community, election participants, and local government agencies, as well as law enforcement agencies conducting cooperation with coordination with law enforcement agencies related to elections.